Economic impact of data localization in five selected African countries. Issue 4 (21st June 2018) - Badran, Mona Farid
Abstract : Purpose: The purpose of this study is to quantify the impact of laws and regulations that govern the cross-border flow of data on the economies of five selected African countries, namely, Egypt, Morocco, South Africa, Kenya and Mauritius. Moreover, this study addresses the state of cloud computing in Africa. Finally, policy recommendations are provided in this respect. Design/methodology/approach: To reach accurate finding the Global Trade Analysis Project (GTAP) data was used, and then the computable general equilibrium (CGE) was computed to estimate the total cost on the economy. Using the three data regulations linkages indexes (DRLs), the increased administrative cost effect was analyzed on five to six major economic sectors in the target countries. This was followed by estimating the loss in sector-wide total factor productivity (TFP) (for the five to six shortlisted sectors). Using this data, the computable general equilibrium model (CGE) was computed, in order to estimate the economy-wide impact. Based on these findings, a set of recommendations were offered to the policy maker, reflecting the obtained results and conclusions and their implications on drafting data-related policies. Findings: The obtained data indexes reveal that Mauritius is the country with the most laws and regulations governing the cross border flow of data, followed by South Africa Egypt to a lesser extent and finally Morocco and Kenya both showing an obvious lack of data regulations. The small value of the estimated elasticity of the selected countries compared to the value of the estimated elasticity in the EU-0.347 shows that the impact of data localization is less in the selected African countries than in the other set of EU countries examined in the research paper. This is because the former has smaller economies with fewer linkages to the global economy and are less reliant on sectors that are heavy users of data. Thus, the overall impact of data localization was not as profound on TFP as is the case in advanced economies. This research paper arrives at the conclusion that fighting the trend of data localization is crucial. In fact, data localization hinders the necessary and essential role of global trade in realizing economic development. Specifically, this is evident in the increase in production costs as reflected in the increase of the prices of goods, which would lead to a decline in incomes. Originality/value: Global studies looked at the impact of data localization on the EU, as well as China, India, Korea and Vietnam, providing some data on Asia Pacific. However, no study has ever been conducted on the Middle East and Africa. This study aims to fill this gap. The approach of this study is to capture the extent of data localization mandates encoded in the laws of each of the selected five African countries showing how these mandates govern their cross-border data flow and, in turn, affect their economies. Furthermore, the policy recommendations section of this research paper makes a contribution to the existing literature.